2019
DOI: 10.3389/fmicb.2019.00394
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights Into Key Plasmodium Proteases as Therapeutic Drug Targets

Abstract: Malaria, caused by protozoan of genus Plasmodium, remains one of the highest mortality infectious diseases. Malaria parasites have a complex life cycle, easily adapt to their host’s immune system and have evolved with an arsenal of unique proteases which play crucial roles in proliferation and survival within the host cells. Owing to the existing knowledge of enzymatic mechanisms, 3D structures and active sites of proteases, they have been proven to be opportune for target based drug development. Here, we disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 106 publications
0
26
0
3
Order By: Relevance
“…An important observation indicated that FPs and other proteases contributing in hemoglobin degradation and egress and de novo RBCs invasion cascade use similar mechanisms for biological control, but use different specific means mediating interactions with their substrates and inhibitors [39] . Also in another review, this extension motif was suggested as a novel anti-malarial drug target [40] .…”
Section: Fp Motifsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important observation indicated that FPs and other proteases contributing in hemoglobin degradation and egress and de novo RBCs invasion cascade use similar mechanisms for biological control, but use different specific means mediating interactions with their substrates and inhibitors [39] . Also in another review, this extension motif was suggested as a novel anti-malarial drug target [40] .…”
Section: Fp Motifsmentioning
confidence: 99%
“…Similar to other papain family plasmodial CPs, the C-terminal of SERAs have an extension motif (10 amino acids) to bind with its substrate [39] . Also, this extension motif was suggested as a novel anti-malarial drug target [40] .…”
Section: D] Serine Repeat Antigens (Seras)mentioning
confidence: 99%
“…They are involved in a number of vital pathways which are essential for parasite survival: red blood cell (RBC) invasion, hemoglobin (Hb) degradation, egress. [3] Among these pathways, Hb degradation provides amino acids necessary to the metabolism and survival of the parasites inside erythrocytes [4][5][6][7], and also reduces the colloidosmotic pressure within the host RBCs and thus preventing their premature lysis. [8,9] One of these attractive protease targets is the Plasmodium falciparum M1 aminopeptidase, PfA-M1.…”
Section: P Falciparum Proteases Have Appeared As Promising Targets Fmentioning
confidence: 99%
“…[10,12,13,18] Given these results, PfA-M1 seems to be an essential protein and hence, a very attractive validated target for the development of novel antiplasmodial drugs. [3,19,36,37] In addition, blocking PfA-M1 catalytic activity with low molecular weight inhibitors is fatal for the parasite without major toxicities for the host. [16,38] Most of the PfA-M1 inhibitors (Table 1) consist of tetrahedral intermediate mimics, such as the well-known aminopeptidase inhibitor bestatin 1, or as phosphinic acid 2, or zinc-chelating group inserted in a peptide-like scaffold, such as hydroxamic acids 3-5.…”
Section: P Falciparum Proteases Have Appeared As Promising Targets Fmentioning
confidence: 99%
“…PLCPs in parasites are also known for their indispensable roles in parasite growth and cell differentiation, signalling and host invasion [ 11 , 13 , 14 , 15 , 16 ]. Their suitability as a potential drug target for antiparasitic chemotherapy is very well validated [ 15 , 17 , 18 ]. Therefore, the design and synthesis of cysteine protease inhibitors (CPIs) holds significant value in medicine and biotechnology.…”
Section: Introductionmentioning
confidence: 99%